Research and justification of parameters for a flexible sectional screw working body - Bulgakov, Volodymyr; Булгаков, Володимир Михайлович; Olt, Juri; Ihnatiev, Yevhen; Ігнатьєв, Євген Ігорович; Holovach, I.; Trokhanyak, O. (My University, 2025)
The article presents a new design of the hinged-sectional working body of a flexible screw conveyor intended for transporting bulk agricultural materials. The influence of the hinge mechanism’s structural parameters on its operational efficiency is investigated, particularly in terms of ensuring the required angular displacement of axes, preventing jamming, and minimizing energy losses. Analytical dependencies are proposed to determine the arc displacement of the ball along friction surfaces, its velocity, and the efficiency coefficient of the hinge mechanism. It is established that the maximum efficiency coefficient ranges between 0.88 and 0.91 when the ratio of the ball radius to the rotation radius of ball centers is within 0.3–0.45. Calculations show that an increase in the conical socket inclination angle leads to a reduction in efficiency. To enhance the overall conveyor efficiency, it is recommended to reduce the hinge axis deviation angle, which results in a larger bending radius of the screw. Specifically, it is determined that the axis deviation angle should not exceed 20–25° while maintaining an efficiency coefficient of at least 0.9. To determine the optimal structural characteristics of the screw working body sections, computer modeling of force load influence on corresponding deformations was conducted. The results show that an increase in torque leads to a greater twisting angle of the section, with the most significant deformation occurring at a minimal number of axial rods. The proposed design improves the efficiency of loading and unloading operations while expanding technological capabilities in transporting grain and other bulk materials.
Keywords: flexible screw conveyor; hinge mechanism; efficiency coefficient; force parameters; computer modeling; bulk material transportation